Influence of physical exercise on activities of daily living in older adults: an empirical analysis based on propensity score matching and difference-in-differences - Ma, Xiaoni; Li, Xiaotian; Che, Li; Dong, Jie (Frontiers in Public Health, 2025)
BackgroundActivities of Daily Living (ADL) are crucial for assessing older adult’s ability to live independently. Physical exercise has a positive impact on ADL. During the COVID-19 pandemic, the reduction of social interaction and the limited use of exercise facilities led some older adults to reduce regular exercise and show more sedentary behavior. This study aimed to examine the influence of physical exercise on the Activities of Daily Living (ADL) among older adults during the COVID-19 pandemic.MethodsUsing the China Longitudinal Aging Social Survey (CLASS) data, propensity score matching (PSM) was performed on the sample, with the interaction between participation in physical exercise and observation year as the core independent variables, and instrumental activities of daily life (IADL) and basic activities of daily life (BADL) as the dependent variables for difference-in-differences (DID) regression analysis. Verify age heterogeneity through grouped regression, and use mediation effect analysis to examine the role of retirement.ResultsIn the context of COVID-19, participation in physical exercise had a positive impact on the IADL and BADL of older adults. The IADL and BADL of older adults who participated in physical exercise were 0.189 and 0.119 units higher than those who did not participate in physical exercise. This positive impact also varied by age, for older adults aged 75 years and above, participation in physical exercise exerted a significant positive impact on both IADL and BADL. In contrast, among those under 75 years of age, no significant effects of physical exercise on IADL or BADL were detected. The analysis further revealed retirement status emerged as a significant masking variable that amplifies observed differences in ADL outcomes when controlled analytically.ConclusionDuring the pandemic, physical exercise still has a positive impact on the IADL and BADL of the older adults. The older adults aged 75 and above are more reliant on physical exercise to improve their IADL and BADL. Due to the survivor effect, the relative negative effect of retirement on the IADL and BADL of the older adults who engage in physical exercise is more pronounced.